Distribusi Cysticercus bovis Pada Sapi Bali Tiga Bulan Pasca Infeksi Telur Taenia saginata (DISTRIBUTION CYSTICERCUS BOVIS ON BALI CATTLE OF EXPERIMENTALLY INFECTED WITH TAENIA SAGINATA THREE MONTHS POST INFECTED) - Diyani, Putu Sita Paramita; Dwinata, I Made; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2015)
Research has been conducted to infect the eggs of Taenia saginata in Bali cattle. This studyaims to determine the location and total distribution of Cysticercus bovis found in each of theselocations 3 months post-infection. This study uses one female Bali cattle, aged six months. TheBali cattle infected with Taenia saginata eggs 500.000 (isolates Bali). Cows was necropsied threemonths (103 days) after infection. Number C. bovis found recorded along with the location and distribution grouped by organ and skeletal muscle infected. Data obtained in the form of numberand location of distribution is presented in a matter of percentages, then the data were analyzeddescriptively. The results showed that a total of 534 C. bovis were found, which are distributed tothe heart (13.7%), diaphragm (16.3%), anterior skeletal muscle (12.7%), posterior (19.1%) and inthe head (38.2%).
Keywords: distribution of Cysticercus bovis; Taenia saginata; bali cattle